Kepemimpinan HJ. Ruminah dalam Pengelolaan Pendidikan Agama Islam di Panti Asuhan Tunas Harapan ‘Aisyiyah Kota Pontianak - Dini Arini (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2022)
The ‘Aisyiyah Tunas Harapan Orphanage in Pontianak City was established as a social welfare institution that is responsible for caring for children in the interior of West Kalimantan who do not have parents or guardians who are unable to provide them with the right to education, clothing, food, and housing. The reason for the establishment of the ‘Aisyiyah Tunas Harapan Orphanage in Pontianak City was that it started from a great social sense and empathy from a female character named Hj. Ruminah. He felt compassion and concern for the condition of the children in the interior of West Borneo at that time, which was around the 1970s. Out of compassion and concern, he helped the children by inviting them to be cared for by him. Not only was he raised, he also taught them, such as adab, Islamic religious education, non-formal education, and informal education. This study uses a qualitative approach with the type of character study research. This study resulted in the finding that the leadership of Hj. Ruminah greatly influences the management of Islamic Religious Education at the ‘Aisyiyah Tunas Harapan Orphanage, Pontianak City. Abstrak:Panti Asuhan ‘Aisyiyah Tunas Harapan Kota Pontianak didirikan sebagai lembaga kesejahteraan sosial yang bertanggung jawab dalam mengasuh anak-anak pedalaman Kalimantan Barat yang tidak memiliki orang tua atau walinya tidak mampu memberikan hak kepada mereka berupa pendidikan, sandang, pangan dan papan. Alasan berdirinya Panti Asuhan ‘Aisyiyah Tunas Harapan Kota Pontianak ialah berawal dari rasa sosial dan empati yang besar dari seorang tokoh perempuan yang bernama Hj.Ruminah. Beliau merasakan iba dan prihatin dengan keadaan anak-anak pedalaman Kalimantan Barat pada saat itu, yakni sekitar tahun 1970-an. Dari rasa iba dan keprihatinannya, beliau membantu anak-anak tersebut dengan mengajak mereka untuk diasuh oleh beliau. Bukan hanya diasuh semata saja, beliau juga mengajarkan mereka, seperti adab, Pendidikan Agama Islam, pendidikan non-formal, dan pendidikan informal. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi tokoh. Penelitian ini menghasilkan temuan bahwa kepemimpinan Hj. Ruminah sangat mempengaruhi pengelolaan Pendidikan Agama Islam di Panti Asuhan ‘Aisyiyah Tunas Harapan Kota Pontianak.